Legal Issues and Emerging Technologies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The nation’s 6,800 plus public transportation agencies need to have access to a program that can provide authoritatively researched, specific studies of legal issues and problems having national significance and application to the public transportation industry. Some legal issues and problems are unique to transit agencies. The TRB Transit Cooperative Research Program's TCRP Legal Research Digest 59: Legal Issues and Emerging Technologies provides transportation attorneys with guidance and resources to assist with these legal changes resulting from the implementation of technology, including regulatory challenges, risk management, cybersecurity, privacy, handling confidential and proprietary information, intellectual property rights, civil rights and environmental justice compliance, labor and employment law, and procurement issues.
Keywords: Transportation and Infrastructure

The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In the face of climate change, technological innovation, and global strategic competition, the U.S. Coast Guard will need to respond to many developments in the maritime domain over the next decade. The Coast Guard likely has sufficient statutory authority to respond to most of these developments, but some developments may call for new or clarified statutory authority as well as coordination with international bodies. Current statutory manning requirements, for example, will limit the Coast Guard’s ability to authorize the regulated use of uncrewed vessels with autonomous systems. New authority may also be needed to establish spaceflight-related safety zones applicable to foreign-flagged vessels within 200 nautical miles of the U.S. coastlines.These are among the findings in TRB Special Report 346: The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs from the Transportation Research Board of the National Academy of Sciences, Engineering, and Medicine.The report emphasizes that in addition statutory authority, the Coast Guard will need key organizational and operational capabilities, including a well-trained workforce, to respond to future challenges. A short video charts the Coast Guard's next decade.
Keywords: Transportation and Infrastructure

Sustainable and Resilient Supply Chains Using Emerging Technologies: Policy Options: Proceedings of a Workshop–in Brief - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The coronavirus disease 2019 (COVID-19) crisis sparked concerns about the vulnerability of supply chains and the significant impact of their disruption on the economy and society within the U.S. and abroad. Issues around global supply chains existed before the pandemic but were also greatly aggravated by it. To consider these issues, the Science and Technology for Sustainability program, in collaboration with the Resilient America Program, Transportation Research Board, and Board on Atmospheric Sciences and Climate at the National Academies of Sciences, Engineering, and Medicine, held a series of four virtual workshops on February 3, 4, 17, and 18, 2021. The workshop series addressed opportunities, challenges and environmental implications of increasing local inclusion and community participation in global value chain networks by using new technologies to strengthen resilience and sustainability in the face of recurring disruptions. The series also explored the feasibility of introducing advanced manufacturing, logistics and decision-making under alternative supply chain scenarios in different sectors, with a view to strengthening the resilience of communities and adopting far more environmentally and economically sustainable consumption and production approaches. This publication summarizes the presentations and discussion of the workshops.
Keywords: Environment and Environmental Studies

Emerging Challenges to Priced Managed Lanes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
There is a wide disparity between the goals that state departments of transportation (DOTs) have for priced managed lanes and the public assumption for those goals. The public tends to be highly skeptical of priced managed lanes because the concept is difficult to explain to a nontechnical audience.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 559: Emerging Challenges to Priced Managed Lanes provides an overview of the state of the practice of how state DOTs address challenges to implementing tolling, or pricing, on their managed lane systems.The synthesis entailed an extensive literature review of 60 publications and over 700 online media articles, a survey distributed to all 50 state DOTs, and a sampling of six case examples that explained specific examples of how agencies addressed challenges.
Keywords: Transportation and Infrastructure

Emerging Hazards in Commercial Aviation—Report 1: Initial Assessment of Safety Data and Analysis Processes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Commercial aviation safety in the United States has improved more than 40-fold over the last several decades, according to industry statistics. The biggest risks include managing safety in the face of climate change, increasingly complex systems, changing workforce needs, and new players, business models, and technologies. TRB Special Report 344: Emerging Hazards in Commercial Aviation—Report 1: Initial Assessment of Safety Data and Analysis Processes is the first of a series of six reports that will be issued from TRB and the National Academies of Sciences, Engineering, and Medicine over the next 10 years on commercial aviation safety trends in the U.S.
Keywords: Transportation and Infrastructure

Guidebook for Managing Data from Emerging Technologies for Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
With increased connectivity between vehicles, sensors, systems, shared-use transportation, and mobile devices, unexpected and unparalleled amounts of data are being added to the transportation domain at a rapid rate, and these data are too large, too varied in nature, and will change too quickly to be handled by the traditional database management systems of most transportation agencies.The TRB National Cooperative Highway Research Program's NCHRP Research Report 952: Guidebook for Managing Data from Emerging Technologies for Transportation provides guidance, tools, and a big data management framework, and it lays out a roadmap for transportation agencies on how they can begin to shift – technically, institutionally, and culturally – toward effectively managing data from emerging technologies.Modern, flexible, and scalable “big data” methods to manage these data need to be adopted by transportation agencies if the data are to be used to facilitate better decision-making. As many agencies are already forced to do more with less while meeting higher public expectations, continuing with traditional data management systems and practices will prove costly for agencies unable to shift.Supplemental materials include an Executive Summary, a PowerPoint presentation on the Guidebook, and NCHRP Web-Only Document 282: Framework for Managing Data from Emerging Transportation Technologies to Support Decision-Making.
Keywords: Transportation and Infrastructure

Existing and Emerging Highway Infrastructure Preservation, Maintenance, and Renewal Definitions, Practices, and Scenarios - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Cooperative Highway Research Program's NCHRP Web-Only Document 272: Existing and Emerging Highway Infrastructure Preservation, Maintenance, and Renewal Definitions, Practices, and Scenarios provides appendices to NCHRP Report 750, Volume 7: Preservation, Maintenance, and Renewal of Highway Infrastructure.
Keywords: Transportation and Infrastructure

Dynamic Curbside Management: Keeping Pace with New and Emerging Mobility and Technology in the Public Right-of-Way, Part 1: Dynamic Curbside Management Guide and Part 2: Conduct of Research Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Dynamic curbside management has been the purview of cities, with much of the relevant research and guidance directed toward local transportation agencies. However, state departments of transportation, metropolitan planning organizations, and other regional agencies can be important partners for these local entities because, in many cases, roadways and other curb zone elements are part of the regional or state network.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 340: Dynamic Curbside Management: Keeping Pace with New and Emerging Mobility and Technology in the Public Right-of-Way, Part 1: Dynamic Curbside Management Guide and Part 2: Conduct of Research Report is designed to help practitioners at state DOTs, MPOs, and local jurisdictions build data-driven understanding, allocation, and operation of the curb based on community values.Supplemental to the document are a Quick Start Summary of the research and a Presentation summarizing the project.
Keywords: Transportation and Infrastructure

Emerging Technologies for Construction Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The uses and levels of maturity of five advanced technology areas visualization and modeling, interconnected technologies, safety technologies, instrumentation and sensors, and unmanned aircraft systems in transportation highway construction projects are documented in TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 534: Emerging Technologies for Construction Delivery. The synthesis also investigates the implementation barriers and success factors for these technology areas and discusses the lessons learned as noted by state DOTs in their effort to study, test, and implement a new construction technology.As the highway construction industry infuses more technologies into the process of project delivery, state DOTs have an opportunity to realize improved project performance regarding cost, schedule, and quality.The Federal Highway Administration (FHWA) Every Day Counts (EDC) initiatives promote the use of various advanced and emerging technologies (e.g., automated machine guidance, unmanned aircraft systems, building information modeling, handheld instruments and devices, and work zone intrusion detection systems).
Keywords: Transportation and Infrastructure

Thought Leader Forum Summary—Emerging Issues for ACRP - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Research Results Digest 28: Thought Leader Forum Summary—Emerging Issues for ACRP summarizes a January 30, 2019, forum to identify the most important issues facing the airport industry within the next 5 to 10 years.The goal of this exercise was to engage the ACRP’s Airport Operations Committee (AOC) directly with other thought leaders in the industry to identify and define high-level emerging critical issues that impact, or will soon impact, the airport industry.The digest describes the results of a pre-Forum survey designed to help shape the Forum discussion, summarizes the results of the forum itself, and explores potential next steps.
Keywords: Transportation and Infrastructure

Emerging Technologies Applicable to Hazardous Materials Transportation Safety and Security - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s Hazardous Materials Cooperative Research Program (HMCRP) Report 4: Emerging Technologies Applicable to Hazardous Materials Transportation Safety and Security explores near-term (less than 5 years) and longer-term (5–10 years) technologies that are candidates for enhancing the safety and security of hazardous materials transportation for use by shippers, carriers, emergency responders, or government regulatory and enforcement agencies.The report examines emerging generic technologies that hold promise of being introduced during these near- and longer-term spans. It also highlights potential impediments (e.g., technical, economic, legal, and institutional) to, and opportunities for, their development, deployment, and maintenance.The research focused on all modes used to transport hazardous materials (trucking, rail, marine, air, and pipeline) and resulted in the identification of nine highly promising emerging technologies.
Keywords: Transportation and Infrastructure

Private Transit: Existing Services and Emerging Directions - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Transit Cooperative Research Program (TCRP) Research Report 196: Private Transit: Existing Services and Emerging Directions provides information about private transit services and ways they are addressing transportation needs in a variety of operating environments. The document contains an overview and taxonomy of private transit services in the United States, a review of their present scope and operating characteristics, and a discussion of ways they may affect the communities in which they operate along with several case studies and other supporting information.Private transit services—including airport shuttles, shared taxis, private commuter buses, dollar vans and jitneys—have operated for decades in many American cities. Recently, business innovations and technological advances that allow real-time ride-hailing, routing, tracking, and payment have ushered in a new generation of private transit options. These include new types of public-private partnership that are helping to bridge first/last mile gaps in suburban areas.The report also examines ways that private transit services are interacting with communities and transit agencies, as well as resulting impacts and benefits.
Keywords: Transportation and Infrastructure

Emerging Technologies for Construction Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 372: Emerging Technologies for Construction Delivery explores the use of five emerging technologies for transportation construction projects: global positioning systems for layout, machine guidance, and quantity tracking; handheld computers for construction records; automated temperature tracking for concrete maturity monitoring; four-dimensional computer-aided drafting modeling for constructability analysis and improved communications; and web-based video cameras for remote project monitoring.
Keywords: Transportation and Infrastructure

Current and Emerging Issues Facing the Airport Industry - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2009)
TRB’s Airport Cooperative Research Program (ACRP) Research Results Digest 5: Current and Emerging Issues Facing the Airport Industry summarizes the program and the process for identifying strategic research areas for use with the FY 2010 ACRP problem statement solicitation process and beyond.In January 2014 RRD 5 was updated with the release of ACRP RRD 20: Taking Inventory of ACRP Research and the Net Challenges Facing the Airport Industry.
Keywords: Transportation and Infrastructure

Transportation Implications of Emerging Economic Development Trends - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 327: Transportation Implications of Emerging Economic Development Trends explores economic development trends and how transportation relates to these trends. The report focuses on business production, inventory, and logistics and distribution trends and practices; site selection research and practices; labor market considerations; urban and rural development practices; and international trade and global market trends and implications.
Keywords: Transportation and Infrastructure

Improving Public Transportation Technology Implementations and Anticipating Emerging Technologies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB’s Transit Cooperative Research Program (TCRP) Report 84, e-Transit: Electronic Business Strategies for Public Transportation Volume 8, Improving Public Transportation Technology Implementations and Anticipating Emerging Technologies explores the value of current technologies used in public transportation, examines methods for improving the success of technology implementation, and reviews five promising emerging technologies with application for transit agencies.The declining costs of communications, data storage, and data retrieval are accelerating the opportunities spawned by the Internet and other information and communications technologies. Choosing and sequencing investments in technologies, processes, and people to reduce costs and increase productivity present challenges to the transit manager, who must weigh the costs, benefits, and risks of changing the ways services are delivered. To assist in meeting such challenges, the TCRP Report 84: e-Transit: Electronic Business Strategies for Public Transportation series documents principles, techniques, and strategies that are used in electronic business for public transportation.Appendices for TCRP Report 84, Volume 8 include the following:* Appendix A: Summary of the Transit Agency Leader Focus Group* Appendix B: Summary of the ITS America 2005 Transit GM Summit
Keywords: Transportation and Infrastructure

Naval Engineering in the 21st Century: The Science and Technology Foundation for Future Naval Fleets -- Special Report 306 - Transportation Research Board (The National Academies Press, 2011)
TRB Special Report 306: Naval Engineering in the 21st Century: The Science and Technology Foundation for Future Naval Fleets examines the state of basic and applied research in the scientific fields that support naval engineering and explores whether Office of Naval Research (ONR) activities, under its National Naval Responsibility for Naval Engineering (NNR-NE) initiative, have been effective in sustaining these fields. The committee developed a series of conclusions and recommendations in five areas--the value of the NNR-NE, the state of science and technology supporting naval engineering, the wholeness of the NNR-NE research portfolio, opportunities for enhancement of research and education, and the effectiveness of the NNR-NE initiative. The report's recommendations are addressed to the administrators of the NNR-NE initiative and of ONR.
Keywords: Engineering and Technology

Preventing Teen Motor Crashes: Contributions from the Behavioral and Social Sciences: Workshop Report - Institute of Medicine; Transportation Research Board; National Research Council (The National Academies Press, 2007)
From a public health perspective, motor vehicle crashes are among the most serious problems facing teenagers. Even after more than six months of being licensed to drive alone, teens are two to three times more likely to be in a fatal crash than are the more experienced drivers. Crash rates are significantly higher for male drivers, and young people in the United States are at greater risk of dying or being injured in an automobile than their peers around the world. In fact, in 2003 motor vehicle crashes was the leading cause of death for youth ages 16-20 in the United States. Understanding how and why teen motor vehicle crashes happen is key to developing countermeasures to reduce their number. Applying this understanding to the development of prevention strategies holds significant promise for improving safety but many of these efforts are thwarted by a lack of evidence as to which prevention strategies are most effective. Preventing Teen Motor Crashes presents data from a multidisciplinary group that shared information on emerging technology for studying, monitoring, and controlling driving behavior. The book provides an overview of the factual information that was presented, as well as the insights that emerged about the role researchers can play in reducing and preventing teen motor crashes.
Keywords: Transportation and Infrastructure; Behavioral and Social Sciences; Health and Medicine

Strategic Issues Facing Transportation, Volume 7: Preservation, Maintenance, and Renewal of Highway Infrastructure - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The transportation industry faces a wide range of plausible future drivers and scenarios that could affect standard practices over the next 30 to 50 years. Because the range of plausible futures over such a long-term period is very broad, making a focused prediction of the implications for highway infrastructure preservation, maintenance, and renewal (PMR) is quite challenging.The TRB National Cooperative Highway Research Program's NCHRP Report 750: Strategic Issues Facing Transportation, Volume 7: Preservation, Maintenance, and Renewal of Highway Infrastructure focuses on the issues affecting the PMR of highway infrastructure. The study places emphasis on preparing for plausible future scenarios and develops a pathway to guide transportation agencies in advancing the implementation of emerging PMR practices through a process involving awareness, advocacy, assessment, adoption, and action planning.The appendices to Parts A and B of this report are available as part of NCHRP Web-Only Document 272: Existing and Emerging Highway Infrastructure Preservation, Maintenance, and Renewal Definitions, Practices, and Scenarios.In addition, there are two guides included within the report that help with the understanding, identification, application, and implementation of emerging PMR practices. They are also available as standalone guides:• Practitioner's Guide to Emerging Highway Preservation, Maintenance, and Renewal Practices• Leadership's Guide to Emerging Highway Preservation, Maintenance, and Renewal Practices
Keywords: Transportation and Infrastructure

Considering the Unbanked in Cashless Fare Payment at Point of Service for Bus/Demand-Response Services - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In recent years, many transit systems have been considering the benefits and challenges of moving to completely cashless fare payments and trying to find innovative solutions to help all their customers.The TRB Transit Cooperative Research Program's TCRP Synthesis 163: Considering the Unbanked in Cashless Fare Payment at Point of Service for Bus/Demand-Response Services is designed to help inform transit systems of the impacts of going cashless. Several emerging trends are identified, including that transit agencies are seeking to understand how many riders are unbanked and how to meet their needs.
Keywords: Transportation and Infrastructure